Formulation of Biostimulants Based on Arbuscular Mycorrhizal Fungi for Maize Growth and Yield - Agbodjato, Nadège Adoukè; Assogba, Sylvestre A.; Babalola, Olubukola Oluranti; Koda, Abdel D.; Aguégué, Ricardos M.; Sina, Haziz; Dagbénonbakin, Gustave Dieudonné; Adjanohoun, Adolphe; Baba-Moussa, Lamine (Frontiers in Agronomy, 2022)
The objective of the study was to evaluate the fertilizing potential of two arbuscular mycorrhizal fungi (Glomeraceae and Acaulosporaceae) native to the rhizosphere soils of Benin in a controlled environment (under greenhouse) and in a field environment. For this purpose, corn seeds were coated with Glomeraceae and Acaulosporaceae strains and then deposited in 5 cm deep holes. Different doses of mineral fertilizer were then applied according to the treatments.The experimental design was a split plot of ten treatments with three replicates in both conditions. Sowing was done following two seeds per pot in the greenhouse and in the field and lasted 30 and 80 days respectively. The data collected were related to growth, yield and mycorrhizal infection of the roots. The results in controlled environment (under greenhouse), show that the plants treated with Acaulosporaceae+25%NPK+Urea significantly improve the height, the diameter at the collar, and the dry subterranean biomass with respective increases of 63.74%, 61.53%, 47.79% except for the leaf area and the dry aerial biomass which were improved by Glomeraceae+25%NPK+Urea with respective increases of 42.66% and 57.2% compared to the control. The results in the field showed that the best maize yields in grain, in dry aerial biomass and dry subterranean biomass were obtained significantly with the Glomeraceae strain 25%NPK+Urea with respective increases of 65.28%, 51.26%, 136.36% compared to the control plants. Also, high values were recorded for the frequency and intensity of mycorrhization with the Glomeraceae strain under greenhouse and field conditions. Mycorrhizal inoculation of maize plants showed a beneficial effect in the field with the Glomeraceae strain in combination with 25% NPK+Urea while the Acaulosporaceae strain with 25% NPK+Urea was more expressed in the greenhouse . These endogenous strains can be used as biostimulants to increase maize productivity while considerably reducing mineral inputs in Benin.